Comprehensive Security in a Multipolar Indo-Pacific: ASEAN’s Balancing Act under Malaysia’s Leadership - Syarifuddin, Kurniawan Firmuzi; Pedrason, Rodon; Mahroza, Jonni; Purwantoro, Susilo Adi (Yayasan Riset dan Pengembangan Intelektual, 2025)
As the Indo-Pacific region undergoes profound geopolitical transformation marked by multipolar rivalries and non-traditional security threats, ASEAN faces a critical moment in redefining its role as a normative and functional convener of regional security governance. This article examines how Malaysia’s 2025 chairmanship of the ASEAN Defence Ministers’ Meeting (ADMM) presents a strategic opportunity to recalibrate ASEAN’s defence mechanisms and reinforce its centrality. By advancing the ASEAN Outlook on the Indo-Pacific (AOIP) through integrative maritime and cyber initiatives, and expanding normative engagement with actors such as the Pacific Islands Forum and the Indian Ocean Rim Association, Malaysia can help operationalise ASEAN’s comprehensive security agenda. The analysis highlights internal challenges—including divergent threat perceptions and capacity gaps—and external pressures from great power competition that risk undermining ASEAN’s cohesion. Drawing on Regional Security Complex Theory, security community theory, and ASEAN’s diplomatic culture, the study argues that institutional evolution does not require abandoning ASEAN’s foundational principles but rather adapting them for contemporary governance. The findings underscore the importance of strategic autonomy, inclusive cooperation, and normative clarity in shaping a resilient and adaptive regional security architecture. Ultimately, Malaysia’s chairmanship should be understood as a moment of normative leadership that can consolidate ASEAN’s credibility and enhance its strategic role in moderating competition, managing risks, and fostering stability in a complex and uncertain Indo-Pacific order.